Designing Urban Soundscape for Various Activities based on Soundscape Expectation - Anugrah Sudarsono; Sugeng Joko Sarwono; Andini Hapsari; Helga Salim (Journal of Visual Art and Design, 2021)
The concept of soundscape aims to provide a more holistic understanding of the acoustic environment by taking several aspects into account, such as human perception, the acoustic environment and the context of the space. The soundscape concept is primarily concerned with the human experience and is considered more effective to access the acoustic quality of urban areas than traditional sound measurement. Soundscape analysis was used in this study to determine the relationship between various activities occurring in urban areas and their associated sound sources. This relationship can be used as design guidance for urban soundscape. The interaction was analyzed using the soundscape expectation approach, which is based on people’s memories of urban areas. The participants of this study were requested to compose an ideal acoustic environment according to their expectation for doing four activities: reading, relaxing, talking with friends, and playing with children. According to the data of the participants’ composition there is no significant difference in the overall sound levels between various activities. As a result, the appropriate acoustic environment cannot be determined solely based on the overall sound level. Individuals have varying expectations of sound sources when engaging in various activities.